Is the Underlying Asset an Effective Source of Trust: Evidence from Indonesian Sukuk Market - Hanafi, Syafiq Mahmadah; Kusuma, Hadri; Fasa, Muhammad Iqbal; Al Hashfi, Rizqi Umar (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2023)
This research aims to investigate stock market reaction toward asset-underlied sukuk in Indonesian Sukuk Market. The novelty of this research is to test the market reaction associated with the issue of the underlying asset on the sukuk. To do that, we use event studies during 15-days pre and 15-days post issuance. There are 34 firms with 84 events from 2008 to 2019. Our results suggest that the sukuk is not statistically meaningful to investors. The shareholders could not have confidence in their funds' underlying assets as collateral for Sukuk's issue. It might still be viewed as bonds and other debt policies by investors. Investors need to be given confidence and secure in their investment, not just underlying asset but by handing over certificates of asset ownership. This study contributes empirical evidence to testing investor reactions to the issuance of guaranteed sukuk with underlying assets.